Urethral Injury After Vaginal Birth and Stress Urinary Incontinence: Bulking Agents are Feasible Options - Barba M; Frigerio M; Melocchi T; De Vicari D; Cola A (Dove Medical Press, 2023)
Marta Barba,1 Matteo Frigerio,2 Tomaso Melocchi,1 Desirèe De Vicari,1 Alice Cola2 1Gynecology and Obstetric Department, University of Milano-Bicocca, Monza, Italy; 2Gynecology and Obstetric Department, Fondazione IRCCS San Gerardo Dei Tintori, Ospedale San Gerardo, Monza, ItalyCorrespondence: Marta Barba, University of Milano-Bicocca, ASST Monza, Ospedale San Gerardo, via G.B. Pergolesi, 33, Monza, 20900, Italy, Tel +39 2339434, Email m.barba8792@gmail.comIntroduction and Hypothesis: Lower urinary tract tears after vaginal delivery are a very rare event, estimated to occur in 0.03- 0.05% of women and may be associated with severe stress urinary incontinence, due to great reduction of urethral resistance resulting in a significant intrinsic urethral deficit. Urethral bulking agents represent an alternative, minimally invasive anti-incontinence procedure in the management of stress urinary incontinence. Our aim is to present the management of severe stress urinary incontinence in a patient with concomitant urethral tear caused by obstetric trauma using a minimally invasive treatment option.Methods: A 39-year-old woman referred to our Pelvic Floor Unit for severe stress urinary incontinence. Our evaluation demonstrated an undiagnosed urethral tear involving the ventral portion of the middle and distal urethra, for about 50% of urethral length. Urodynamic evaluation confirmed the presence of severe urodynamic stress incontinence. After proper counseling, she was admitted to mini-invasive surgical treatment with urethral bulking agent injection.Results: The procedure was completed in 10 minutes and she was successfully discharged home on the same day, and no complications occurred. The treatment resulted in total relief of urinary symptoms, which persists at 6-month follow-up.Conclusion: Treatment with urethral bulking agent injection represents a feasible mini-invasive option to manage stress urinary incontinence related to urethral tears.Keywords: urinary incontinence, bulking agents, obstetric tear, pelvic floor ultrasound